The significance of stereotyped B-cell receptors in chronic lymphocytic leukemia - Darzentas, Nikos; Stamatopoulos, Kostas (Hematology/oncology clinics of North America, 2013)
Roughly 30% of patients with chronic lymphocytic leukemia (CLL) carry immunoglobulin receptors with highly similar primary sequences. Highly similar, quasi-identical immunoglobulins are termed stereotyped. Patients with CLL can be assigned to different subsets expressing different types of stereotyped immunoglobulin receptors. Reliable identification of stereotypy may assist in the molecular classification of CLL and thus better-guided, compartmentalized research. In several major subsets, stereotypy extends from shared primary sequences to shared clinicobiological features and outcome. Reliable identification of stereotypy in CLL may pave the way for tailored treatment strategies applicable to each major stereotyped subset.
Keywords: Antibody Diversity; Immunoglobulin Heavy Chains; rozmanitost protilátek; imunoglobuliny; chronická lymfatická leukemie; Somatic Hypermutation, Immunoglobulin; Receptors, Antigen, B-Cell; zvířata; somatická hypermutace imunoglobulinových genů; variabilní oblast imunoglobulinu; těžké řetězce imunoglobulinů; Humans; Immunoglobulins; Leukemia, Lymphocytic, Chronic, B-Cell; receptory antigenů B-buněk; Immunoglobulin Variable Region; lidé; Animals